2022
DOI: 10.1253/circj.cj-21-0816
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Different Versions of the Model for End-Stage Liver Disease Score and Contrast-Associated Acute Kidney Injury in Patients Undergoing Elective Percutaneous Coronary Intervention

Abstract: Background: Pre-procedure liver dysfunction was associated with acute kidney injury after percutaneous coronary intervention (PCI). The aim of this study is to assess and compare the predictive value of different liver function scoring systems for contrastassociated acute kidney injury (CA-AKI) in patients undergoing elective PCI. Methods and Results:A total of 5,569 patients were retrospectively enrolled. The model for end-stage liver disease (MELD) including albumin (MELD-Albumin) score (AUC=0.661) had the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In addition, the results of the Kaplan-Meier analysis indicated that in-hospital mortality following ITVR was higher in high MELD-albumin group than low MELD-albumin group (p = 0.0017; Figure 2D), which further demonstrated the prognostic value of MELD-albumin. In addition, cutoff values from previous studies were selected for sensitivity analysis (9,16). The Kaplan-Meier analysis showed that the probability of in-hospital mortality was significantly higher in patients with high MELD-albumin score based on the cutoff values from other studies (Supplementary Figure 1).…”
Section: In-hospital Survival Analysismentioning
confidence: 99%
“…In addition, the results of the Kaplan-Meier analysis indicated that in-hospital mortality following ITVR was higher in high MELD-albumin group than low MELD-albumin group (p = 0.0017; Figure 2D), which further demonstrated the prognostic value of MELD-albumin. In addition, cutoff values from previous studies were selected for sensitivity analysis (9,16). The Kaplan-Meier analysis showed that the probability of in-hospital mortality was significantly higher in patients with high MELD-albumin score based on the cutoff values from other studies (Supplementary Figure 1).…”
Section: In-hospital Survival Analysismentioning
confidence: 99%